Left ventricular regional dyssynchrony predicts improvements in moderate ischaemic mitral regurgitation after off-pump coronary artery bypass. (12th February 2018) - Sun, Xiaotian; Huang, Guoqian; Huang, Jiechun; Shi, Meng; Wang, Fangrui; Pang, Liewen; Wang, Yiqing
Abstract: OBJECTIVES: The aim of this study was to explore the predictors of the improvement in moderate ischaemic mitral regurgitation (IMR) after off-pump coronary artery bypass grafting (OPCAB) focusing on left ventricular (LV) dyssynchrony. METHODS: A prospective study was performed among 135 patients (age at surgery, mean ± SD: 67.0 ± 8.2 years, 33.3% women) with prior myocardial infarction and moderate IMR undergoing OPCAB from 2008 to 2015. Preoperative and follow-up clinical and echocardiographic parameters were analysed, focusing on LV global/regional dyssynchrony. Patients were grouped by IMR at 1 year postoperatively: improved group with no or mild IMR ( n = 61) and failure group with moderate or severe IMR ( n = 67). Data were compared between groups to explore the predictors of IMR improvement after OPCAB. RESULTS: Seven patients who died before the 1-year postoperative assessment were excluded. At the 1-year follow up, there were 61 patients in the improved group and 67 patients in the failure group. Preoperatively, the improved group had smaller LV global dyssynchrony, LV regional dyssynchrony (papillary muscle systolic dyssynchrony; improved group versus failure group: 48.5 ± 4.5 ms vs 57.1 ± 3.9 ms; P < 0.001) and greater LV ejection fraction (improved group versus failure group: 44.7 ± 5.0% vs 36.7 ± 6.7%; P < 0.001) than the failure group. Papillary muscle systolic dyssynchrony (odds ratio 1.556, 95% confidence interval 1.313–1.845; P < 0.001) and preoperative ejection fraction (odds ratio 0.799, 95% confidence interval 0.691–0.924; P = 0.002) were independent predictors of moderate IMR improvement after OPCAB. CONCLUSIONS: In the selected patients, preoperative moderate IMR could be relieved by coronary artery bypass grafting. Greater ejection fraction and absence of LV regional dyssynchrony may predict the improvement in moderate IMR after coronary artery bypass grafting, suggesting that LV dyssynchrony especially regional dyssynchrony and preserved ventricular function would be important to the outcome of patients with moderate IMR.